2014
DOI: 10.1007/s00603-014-0645-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Advance Rate on Entrapment Risk of a Double-Shielded TBM in Squeezing Ground

Abstract: Shielded tunnel boring machines (TBMs) can get stuck in squeezing ground due to excessive tunnel convergence under high in situ stress. This typically coincides with extended machine stoppages, when the ground has sufficient time to undergo substantial displacements. Excessive convergence of the ground beyond the designated overboring means ground pressure against the shield and high shield frictional resistance that, in some cases, cannot be overcome by the TBM thrust system. This leads to machine entrapment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This model is implemented in FLAC 3D and has been previously used in many numerical simulations (e.g. Barla et al 2007, 2011, Pellet 2009, Sharifzadeh et al 2013, Hasanpour et al 2015.…”
Section: Monitoring Data and Data Processing In The Safety Gallerymentioning
confidence: 99%
“…This model is implemented in FLAC 3D and has been previously used in many numerical simulations (e.g. Barla et al 2007, 2011, Pellet 2009, Sharifzadeh et al 2013, Hasanpour et al 2015.…”
Section: Monitoring Data and Data Processing In The Safety Gallerymentioning
confidence: 99%
“…Generally, the Young's modulus of rock mass was often assumed to be uniform in the ground reaction analyses (Graziani et al, 2005;Hasanpour et al, 2015). However, it was observed that the Young's modulus around an excavation was not constant, but rather non-uniform (Zhang et al, 2012;Cai et al, 2015).…”
Section: Relation Of Confining Pressure and Young's Modulusmentioning
confidence: 99%
“…For a general excavation, the confining pressure (minor principal stress) acting on the excavation surface is zero. It increases gradually with the increasing distance between the element and the excavation surface, and will reach a constant value at locations far away from the excavation (Carranza et al, 1999;Hasanpour et al, 2015). Hence, it is necessary to consider the stress field change in the rock mass surrounding the excavation to accurately predict the ground response, especially in deep buried excavations.…”
Section: Introductionmentioning
confidence: 99%
“…The goal of the present study is to approach the problem of estimating F f from several sides. It is emphasized that this study considers the topic of shield friction in non-squeezing, hard rock conditions (for squeezing conditions, see, e.g., Hasanpour et al (2014); Hasanpour et al (2015); Hasanpour et al (2018); Mohammadzamani et al (2019); Anagnostou (2010, 2011); Zhang and Zhou (2017)). First, theoretical considerations on the interaction between a TBM's shield and the surrounding rock mass are presented (Sect.…”
Section: Introductionmentioning
confidence: 99%